ANALISIS KEPUASAN PENGUNJUNG TERHADAP FASILITAS EKOWISATA HOLIDAY RESORT AEK RASO DI KABUPATEN LABUHAN BATU SELATAN - Andi Fauzan R. Pohan (Jurnal Mahasiswa Akuntansi Samudra, 2023)
Ecotourism is a form of travel to natural areas that is carried out with the aim of conserving the environment and preserving the life and well-being of the local population. The Elephant Holiday Resort Training Center is one of the natural Ecotourism in Labuhan Batu Selatan, therefore this type of tourism must be developed specifically to support the preservation of the surrounding forest habitat. Because visitor visits are influenced by visitor satisfaction which will determine how long a visitor visits to the ecotourism area. Then satisfaction becomes the main priority in its management, service quality is also related to the provision of adequate facilities and management of facilities both in quality and quantity which will greatly affect visitor satisfaction and interest in the next visitor visit. Ecotourism facilities have a very positive and significant effect on visitor satisfaction and the development of facilities besides that facilities are also one of the important things for developing tourism. The results of the data were analyzed using multiple linear analysis. The results of this studied explain that attractiveness, the existence of good and adequate facilities, and visitor knowledge will affect visitor satisfaction by 73.3%. In other words, there is the influence of other variables of 26.7% which are not measured in this study.